Light in architecture the intangible material - Ramos, Elisa Valero (RIBA Publishing, 2015)
"Light in Architecture explores the role and use of light in and around buildings from the time that Stonehenge was built through to the present day, illustrating how a greater understanding of this intangible and free material will lead us to better architecture and, ultimately, improve our quality of life. Translated and carefully updated from the best-selling Spanish book, La Materia Intangible, this full colour edition explains why light is so fundamental to human perception, how its nature and use are influenced by time and place, and how it has come to be used as a tool for abstract architectural design. Drawing on centuries of thinking and over 40 real-life, international exemplars, the book explores the different ways that light can be harnessed and manipulated to achieve particular objectives, emotions or experiences, as well as how the technologies and techniques for doing so have developed over time"--Provided by publisher.